Evaluasi Pembelajaran Pendidikan Jasmani pada Situasi Pandemi Covid-19 di SMA Negeri 1 Bobotsari - Dea Tara Deninta; Rumini Rumini (Universitas Negeri Semarang, 2022)
This research aims to find out the picture of physical education learning and the obstacles faced during the COVID-19 pandemic at Sma Negeri 1 Bobotsari. This type of research is qualitative research with descriptive shortness. The location of this research was carried out at State High School 1 Bobotsari Purbalingga Regency of Central Java Province. The data collection techniques in this study used observation, interview and documentation techniques. As for data analysis using data reduction techniques, data presentation and conclusion withdrawal. The results showed that the implementation of physical education online learning at N 1 Bobotsari High School went quite well and was able to use online learning media such as Mobile Phones and Laptops with applications used including Google classroom, Quizizz, Quipper, Telegram and WhatsApp. The obstacle faced is that there are students who are absent without following online learning. In addition, video conferences have not been able to be implemented, namely power outages, difficulty signaling and running out of internet data quotas. The conclusion in this study is that the implementation of physical education courageous learning at SMA N 1 Bobotsari by teachers and students has gone well and is able to use online learning media such as cellphones and laptops with the learning model used using a command or command system.